Soluble urokinase-type plasminogen activator receptor (suPAR) is associated with risk for thromboembolic complications and mortality in patients with COVID-19. (14th October 2021) - Luo, S; Samelko, B; Du-Fay-De-Lavallaz, J M; Gomez, J M D; Zemke, A M; Suboc, T; Williams, K A; Fugar, S; Simmons, J A; Volgman, A S; Hayek, S; Reiser, J
Abstract: Background/Introduction: The high prevalence of thromboembolism in patients with COVID-19 causes significant morbidity and mortality. The soluble urokinase-type plasminogen activator receptor (suPAR), a known inflammatory and immune mediator in several renal and cardiovascular conditions, has recently been shown to correlate with acute kidney injury and severe respiratory failure in COVID-19. To date, no study has investigated the association between suPAR and thromboembolism in COVID-19. Purpose: To evaluate associations between suPAR, thromboembolic complications, and mortality in COVID-19. Methods: We conducted a retrospective cohort study of a random sample of 109 patients among those hospitalised at a tertiary medical centre comprising three hospitals between March and June 2020 for COVID-19 who had blood samples collected and stored on admission. Serum suPAR was measured using a commercially available enzyme immunoassay. Baseline (hospital admission) variables extracted from electronic medical records included age, sex, race/ethnicity, body mass index (BMI), history of cardiovascular disease (including deep venous thrombosis [DVT] and pulmonary embolism [PE]), serum creatinine, serum D-dimer, incident DVT/PE, and death during hospitalization. Patients were subsequently grouped by suPAR quartiles. Associations between suPAR, thromboembolic complications (PE and/or DVT), and overall mortality were evaluated using multivariable logistic regression. Results: Among the 109 patients, mean age was 56 (standard deviation [SD], 16) years, 34 (39%) were women, mean BMI was 35 (SD, 8) kg/m 2, 78 (71%) had coexisting cardiovascular disease, median creatinine level was 1.2 (interquartile range [IQR]: 0.8–2.3) mg/dl, median D-dimer level was 1.5 (IQR, 0.8–6.4) μg/ml, and median suPAR level was 10.1 (IQR: 4.1–14.4) pg/mL. Seven (6%) patients were found to have PE, 18 (17%) developed PE/DVT, and 22 (20%) died during the admission (Table). Per quartile higher suPAR level, there was higher risk for PE or DVT (OR=2.02, 95% CI 1.07–3.83, p=0.03). Compared to those in the lowest suPAR quartile, patients in the highest quartile had 11.1 times higher risk for PE/DVT (OR=11.1, 95% CI 1.51–81.8, p=0.02, Figure). SuPAR is also associated with overall mortality, with 2.25 times higher risk of death seen per quartile increase in suPAR level (OR= 2.25, 95% CI 1.24–4.06, p=0.007). Conclusion: Higher suPAR levels at the time of hospital admission is associated with higher risk for thromboembolic complications i.e., PE and DVT, as well as mortality in patients with COVID-19. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Rush University Medical Center